Examining the Associations Among Attachment, Affective State, and Romantic Relationship Quality. (January 2015) - Meyer, Dixie D.; Jones, Melissa; Rorer, Alisha; Maxwell, Kelly
This study examined the direct and indirect associations between insecure attachment patterns (avoidant and anxious) and affective state (positive and negative) on romantic relationship quality with a sample of 572 individuals involved in a romantic relationship. Results from structural equation model analyses indicated a negative direct association between insecure attachment patterns and romantic relationship quality as well as positive affective state. Thus, insecure attachment behavioral patterns were associated with reduced romantic relationship quality and positive emotions. Positive direct associations were found between positive affective state and romantic relationship quality; thus, positive emotions were associated with greater perceived romantic relationship quality. A positive direct association was also observed between anxious attachment patterns and negative affective state; thus, negative emotions were associated with the insecure, anxious attachment behavioral patterns. Application of the findings lends to the importance of emotion-focused intervention in clinical practice.